Assessment of Translocator Protein Density, as Marker of Neuroinflammation, in Major Depressive Disorder: A Pilot, Multicenter, Comparative, Controlled, Brain PET Study (INFLADEP Study) - Yrondi, Antoine; Aouizerate, Bruno; El-Hage, Wissam; Moliere, Fanny; Thalamas, Claire; Delcourt, Nicolas; Sporer, Marie; Taib, Simon; Schmitt, Laurent; Arlicot, Nicolas; Meligne, Deborah; Sommet, Agnes; et al. (Frontiers in Psychiatry, 2018)
Background: Major depressive disorder (MDD) is a serious public health problem with high lifetime prevalence (4.4–20%) in the general population. The monoamine hypothesis is the most widespread aetiological theory of MDD. Also, recent scientific data has emphasized the importance of immuno-inflammatory pathways in the pathophysiology of MDD. The lack of data on the magnitude of brain neuroinflammation in MDD is the main limitation of this inflammatory hypothesis. Our team has previously demonstrated the relevance of [18F] DPA-714 as a neuroinflammation biomarker in humans. We formulated the following hypotheses for the current study: (i) Neuroinflammation in MDD can be measured by [18F] DPA-714; (ii) its levels are associated with clinical severity; (iii) it is accompanied by anatomical and functional alterations within the frontal-subcortical circuits; (iv) it is a marker of treatment resistance. Methods: Depressed patients will be recruited throughout 4 centres (Bordeaux, Montpellier, Tours and Toulouse) of the French network of 13 expert centres for resistant depression. The patient population will be divided into 3 groups: i) experimental group – patients with current MDD (n=20), ii) remitted depressed group – patients in remission but still being treated (n=20); and, iii) control group without any history of MDD (n=20). The primary objective will be to compare PET data (i.e. distribution pattern of neuroinflammation) between the currently depressed group and the control group. Secondary objectives will be to: i) compare neuroinflammation across groups (currently depressed group vs remitted depressed group vs control group); ii) correlate neuroinflammation with clinical severity across groups; iii) correlate neuroinflammation with MRI parameters for structural and functional integrity across groups; iv) correlate neuroinflammation and peripheral markers of inflammation across groups. Discussion: This study will assess the effects of antidepressants on neuroinflammation as well as its role in the treatment response. It will contribute to clarify the putative relationships between neuroinflammation quantified by brain neuroimaging techniques and peripheral markers of inflammation. Lastly, it is expected to open innovative and promising therapeutic perspectives based on anti-inflammatory strategies for the management of treatment-resistant forms of MDD commonly seen in clinical practice. Trial registration: NCT03314155